Pengaruh Rasio Campuran Etanol-Air sebagai Pelarut Ekstraksi terhadap Mutu Ekstrak Herba Meniran (Phyllanthus niruri Linn.) - HARRISUL RIVAI; HAZLI NURDIN; HAMZAR SUYANI; AMIN BAKTIAR (JURNAL ILMU KEFARMASIAN INDONESIA, 2010)
Effects of ratios of ethanol-water as extracting solvent in obtaining extractable material, phenolic compounds and antioxidant activity from the herb of Phyllanthus niruri Linn. have been investigated. The ratios tested were 100:0, 80:20, 70:30, 60:40 and 50:50. The results revealed that the ratio of ethanol-Water used gave significant effect on extractable material, phenolic compounds and antioxidant activity (p<0.05). Among the ratios tested, the best result was obtained by ethanol-water of 60:40 as extracting solvent for the herb of Phyllanthus niruri Linn. to obtain phenolic compound which has antioxidant activity.